Organizational Leadership Strategies in Improving the Quality of School Education in the Digital Era - Yusmansyah*, Erfizal Fikri; Sulyani, Agnesia Candra; Larasati, Niken; Nurhasanah, Hasna; Nisa, Choirun; Firdaus, Ahmad Rizki (Riwayat: Educational Journal of History and Humanities, 2024)
This research explores the function of leadership in the digital age. Educational institutions, especially secondary schools, need to adapt to the rapid development of technology. The quality of education is important to keep pace with the high demand for human resources in the future. The Indonesian Ministry of Education states that there are four competencies (4C) that students must have in facing the digital era, namely critical thinking and problem solving, creativity and innovation, collaboration, communication. The quality of organizational leadership in the secondary school environment is determined by the leadership of the principal. This research concludes that school quality is determined by instructional and transformational principal leadership strategies. These two types of leadership can influence teacher performance indirectly through changes in school climate. Improved teacher performance has a direct impact on student performance. Thus, principals' instructional and transformational leadership strategies are the main factors in determining the quality of secondary school education in the digital era.